Impact of Refined Boundary Conditions of Land Objects on Urban Hydrological Process Simulation - Chaohui Chen; Yindong Zhang; Yihan Lou; Ziyi Tang; Pin Wang; Tangao Hu (Land)
Urbanization has led to an increase in impervious areas and, consequently, an increase in the surface runoff volume and runoff rate. This has exacerbated urban flooding and highlighted the importance of modeling urban hydrological processes. The Waterview Community of Hangzhou City (WCHC) was taken as the study area, and three scenarios were developed: the original scenario, the rough description scenario, and the fine description scenario. The urban hydrological processes were simulated through a coupled model incorporating actual measurements and four design precipitation events (1-year, 5-year, 10-year, and 20-year return periods). The results show the following: (1) The refined depiction scenario has the highest accuracy in terms of measured precipitation, with an average error of 0.54 cm. (2) During different precipitation return periods, the refined depiction scenario shows the smallest range of accumulated water, with a more realistic distribution. On average, it differed from the original scenario by 21.45% and from the rough depiction scenario by 32.18%. (3) The simulation results after the refinement of the feature boundaries are more reasonable in terms of the flow rate and flow direction, indicating that the simulation results have better dynamics. The results showed that refined boundary conditions improved the accuracy and dynamics of urban hydrological simulations, especially in terms of their reflection of actual water accumulation under varying precipitation conditions.